Green technology to optimize the extraction process of turmeric (Curcuma longa L.) oils - Tran, Thien Hien; Nguyen, Phu Thuong Nhan; Pham, Tri Nhut; Nguyen, Duy Chinh; Dao, Tan Phat; Nguyen, Trinh Duy; Nguyen, Dai Hai; Vo, Dai-Viet N.; Le, Xuan Tien; Le, Nhan Thi Hong; Bach, Long Giang (IOP Publishing, 2019)
Turmeric oil has many uses in the field of medicine and food. There are many methods of extracting essential oils from plants. However, every traditional method has limitation regarding the heat transfer, time or quality of the oil obtained. In this study, the combination of microwave extraction and response surface methodology are used to extract turmeric oil and optimize the factors that influence the extraction process. The results showed that optimal influencing factors such as the ratio of water to the raw materials were 2.99:1 (mL/g), the microwave power used at 456.60 (W) for the extraction time was 102.43 (min) for the essential oil yield of 0.95 (%) with 100 % reliability.